Dissemination of Light Reflection Teaching Aids as an Effort to Improve the Quality of Science Learning at Mi Nurul Huda, Pulutan, Nogosari, Boyolali - Hidayah, Fatimah Nur; Jamaldi, Agus; Ardiyanto, Farit; Krisitiawan, Samuel Ardhi; Tamzil, Oliver Kurniaawan (Jurnal Pengabdian Masyarakat MIPA dan Pendidikan MIPA, 2024)
MI (Madrasah Ibtidaiyah) Nurul Huda represents a formal educational institution situated in Pulutan Village, Nogosari District, Boyolali Regency. The institution offers a comprehensive curriculum encompassing general education and Islamic religious studies. Notably, the school includes science as one of its core subjects. Through interviews with stakeholders, particularly Mrs. Basuki, it has been identified that the current challenge faced by the school is the effective dissemination of science knowledge to students. This predicament arises from the limited availability of science teaching aids, hindering the practical delivery of educational material. The primary objective of this Community Service Program (PKM) is to facilitate the distribution and training in the utilization of light-reflecting props at MI Nurul Huda. The initiative aims to address the aforementioned challenge by providing teachers with valuable tools to enhance the practicality of material delivery, with a specific focus on the topic of light reflection. It is anticipated that the incorporation of these teaching aids will not only assist educators in conveying scientific concepts effectively but will also contribute to a more accessible learning experience for the students